Atividade antileishmania de extrato bruto e de substâncias isoladas de Porophyllum ruderale (Jacq.) Cass. em Leishmania amazonensis - Takahashi, Helena Teru (2011)
Leishmaniasis are diseases caused by protozoa of the genus Leishmania. This group of diseases have a worldwide distribution on five continents, occurs in 88 countries and is prevalent in tropical and subtropical regions. The WHO estimates that 2 million new cases occur annually. They are classified in American Cutaneous Leishmaniasis (ACL) and Visceral Leishmaniasis (VL). In Brazil, the American cutaneous leishmaniasis is one of dermatological disorders that deserves more attention because of its magnitude, as well as the risk of deformities that can produce in human. The chemotherapy for this disease is mainly based on pentavalent antimonials, but amphotericin B and pentamidine can be used as second choice. The challenge is still large in relation to the discovery of an ideal drug (low cost, efficient, easy administration and low toxicity) and its pharmacokinetics, because of the widespread nature and location of the intracellular parasite. So, there is an urgent need to develop an appropriate drug therapy and the study of bioactive substances in plant species, an interesting alternative, since Brazil has a wide biodiversity. Among plants, there is the kind Porophyllum ruderale (Jacq.) Cass., commonly used on injuries caused by protozoa of the genus Leishmania. The objectives of this work were to prepare the crude extract of aerial parts of P. ruderale, fractionate and isolate substances; to evaluate the antileishmanial activity and cytotoxicity of crude extract and isolated compounds from P. ruderale and to check the effect of these compounds on morphology, ultrastructure, mitochondria and cytoplasmic membrane of L. amazonensis. The crude extract showed IC50 values of 60.3±9.2 and 77.7±7.7 μg/mL, respectively, against promastigote and axenic amastigote forms. We isolated and identified by chromatographic and spectrometric methods and mass spectroscopy, two thiophenes derivatives: 5-methyl-2, 2 ': 5', 2''-terthiophene (compound A) and 5'-methyl-[5-(4-acetoxy-1-butinil)] -2,2 'bi-thiophene (compound B). The CC50 value of dichloromethane extract was 500±50 μg/mL on J774G8 macrophages. Compound A showed IC50 values of 7.7±1.7, 19.0±4.7 and 37±0 μg/ml for promastigote, axenic amastigote and intracellular amastigote forms of L. amazonensis, respectively, and CC50 value of 370±50 μg/mL on J774G8 macrophages. The compound B showed IC50 values of 21.3±4.4, 28.7±2.6 and 51±0 μg/ml for promastigotes, axenic amastigote and intracellular amastigote L. amazonensis, respectively, and CC50 value of 335±15 μg/ml on J774G8 macrophages. The compounds A and B showed hemolytic index lower than 10%, at a concentration of 500 μg/mL. Cells of L. amazonensis treated with compounds A and B and labeled with rhodamine 123 indicated mitochondrial membrane depolarization caused by the compound A. On the other hand, treatment with compounds A and B and labeling with propidium iodide indicated no change in the cytoplasmic membrane. Treatment of cells of L. amazonensis with compound A caused morphological changes under a scanning electron microscope (SEM) and Transmission Electron Microscopy (TEM) indicated ultrastructural changes in mitochondria of the parasite. Cells of L. amazonensis treated with compound B showed morphological changes by SEM, however, there were no ultrastructural changes by TEM. Further studies should be realized to elucidate the mechanism of action of thiophenes derivatives isolated from the species P. ruderale, which may contribute to the development of new drugs for the treatment of leishmaniasis.